Rekonstruksi Identitas, Relasi Kuasa, dan Agensi Perempuan dalam Novel Berlatar Pesantren Perspektif Stuart Hall - Chotimah, Dien Nur; Susilowati, Meinarni; Khonsa, Nabila Nur (ppjbsip, 2025)
Novels set in Islamic boarding schools often represent women through religious and cultural discourses that normalize obedience and morality, so the construction of female identity within them has not been studied in depth. Previous studies have been more descriptive or normative, so they have not been adequate in discussing female identity formed through representational practices in literary texts. This study aims to analyze the reconstruction of female identity in the novel Dua Barista through narrative and dialogical representation using Stuart Hall's theory of representation and cultural identity. This study uses a qualitative method with a text analysis approach based on cultural studies. Data were obtained from the dialogue and narrative of the two main female characters, Mazarina and Maesaroh. Data analysis was conducted through Stuart Hall's interpretive qualitative analysis, covering representation, discourse, identity as a process, and articulation. The results show that female identity is constructed as a dynamic cultural and discursive process, shaped by dominant discourses on morality and religious obedience, while simultaneously opening up space for situational articulation of agency through negotiation of meaning. Power relations work productively through religious language and symbols in shaping the subjectivity of Islamic boarding school women. This research has implications for strengthening the study of Islamic boarding school literature based on a cultural-critical approach and expanding the discourse on gender and identity in the context of religious literature in Indonesia. AbstrakNovel berlatar pesantren kerap merepresentasikan perempuan melalui diskursus religius dan kultural yang menormalisasi kepatuhan dan moralitas, sehingga konstruksi identitas perempuan di dalamnya belum dikaji secara mendalam. Kajian sebelumnya lebih banyak bersifat deskriptif atau normatif, sehingga belum memadai dalam membahas identitas perempuan yang dibentuk melalui praktik representasi pada teks sastra. Penelitian ini bertujuan untuk menganalisis rekonstruksi identitas perempuan dalam novel Dua Barista melalui representasi naratif dan dialogis dengan menggunakan teori representasi dan identitas budaya Stuart Hall. Penelitian ini menggunakan metode kualitatif dengan pendekatan analisis teks berbasis cultural studies. Data diperoleh dari dialog dan narasi dua tokoh utama perempuan Mazarina dan Maesaroh. Analisis data dilakukan melalui analisis kualitatif interpretatif Stuart Hall, meliputi representasi, diskursus, identitas sebagai proses, dan artikulasi. Hasil penelitian menunjukkan bahwa identitas perempuan dikonstruksi sebagai proses kultural dan diskursif yang dinamis, dibentuk oleh diskursus dominan tentang moralitas dan kepatuhan religius, sekaligus membuka ruang artikulasi agensi yang bersifat situasional melalui negosiasi makna. Relasi kuasa bekerja secara produktif melalui bahasa dan simbol religius dalam membentuk subjektivitas perempuan pesantren. Penelitian ini berimplikasi pada penguatan kajian sastra pesantren berbasis pendekatan kultural-kritis serta memperluas diskursus tentang gender dan identitas dalam konteks sastra religius di Indonesia.